Macronutrients, Moisture And Ash Content Analysis In Gluten-Free Fettuccine Made From Sorghum Flour With Mung Bean Flour Substitution - Nunciata, R. Rr. Athiyah Pavita (Jurnal Gizi dan Kesehatan Nusantara, 2024)
The increasing of public awareness about health and gluten-sensitivity has create a development and increasing consumption of gluten-free food. Sorghum is one of the gluten-free food sources that rich in fiber and antioxidant. Mung beans are rich in protein and other beneficial micronutrients. The aim of this study is to discover the macronutrient content, moisture content, and ash content of gluten-free fettuccine based on sorghum flour with mung bean flour substitution. This study is experimental research on the development of the gluten-free fettuccine. The formula of sorghum flour and mung bean flour used in this study is 60:40, with additional ingredients including eggs, xanthan gum, oil, and salt. Subsequently, laboratory test was conducted on the raw gluten-free fettuccine using the proximate analysis method. The results of the analysis showed that 50 grams of gluten-free fettuccine contained 61,60% carbohydrates, 11,81% protein, 5,64% fat, 19,62% moisture, and 1,02% ash content. The high moisture content is due to the fact that the study did not include the drying stage of the product. Additionally, there are advantages and disadvantages of the gluten-free fettuccine compared to SNI (Indonesian National Standard) quality standards and other commercial products. The advantage of this research product is that it uses gluten-free main ingredients. The disadvantages of the gluten-free fettuccine in this study are the relatively high ash content, which does not meet SNI quality standards.